Rasgos de personalidad en la elección profesional de los estudiantes de la Unidad Educativa Juan de Velasco - Paguay Allauca, Jenny Johana (2021)
The aim of this research was to analyze the importance and correlation of personality traits on professional choice of students on the third year of high school at " Juan de Velasco" Educational Unit. Personality defines the person and the physical, genetic and social characteristics defining the temperament and the acquired character; while the professional choice is a complex decision in which both individual and social factors are involved. The methodology used had a quantitative approach, with a non-experimental design, its type was basic, bibliographic field and correlational, the population was students of third year of high school, its non-probabilistic and intensional sampling, formed by 85 males and 125 females, the techniques psychometric tests and its instruments the Test 16PF, where 27% have developed a factor of hardness, with the TEST RGO most of them have more interest and aptitudes, for medicine and health sciences with 34% and 35%; By means of SPSS, we found a Pearson correlation of 0. 199**, with a significance of 0.004, with a conclusion that analyzes that personality is a significant factor in decision making in the professional choice, being agreeableness and self-control the most prevalent traits and directly related to the aptitude and interests required in the careers of medicine and health sciences.